Refined risk assessment and differentiated protection of lightning damage in distribution network lines considering the underlying surface environment - Wan, Ziyang; Fu, Lixiang; Du, Zhenchuan; Chen, Zhigang; Liu, Chao; Zhu, Yi; Ma, Xiaoxin (Frontiers in Energy Research, 2024)
The distribution line is widely distributed and the span of pole-towers is small. However, the existing lightning positioning system has limited positioning accuracy, and the lightning strike coordinates it locates have certain deviations for the distribution network. The lightning hazard risk divided by lightning density is not sufficient to support the differentiated lightning protection transformation of the distribution network. The environment of the underlying surface where the pole-tower is located has a significant impact on lightning activity, so this paper combines terrain, climate, lightning current characteristics, and historical lightning trip data to finely evaluate the lightning risk level in the distribution line pole-tower area. This paper provides a detailed analysis of the relationship between different underlying surface environments and lightning current characteristics and utilizes the entropy weight method to construct a comprehensive lightning disaster risk index, then evaluates the risk level of lightning disaster in different regions, and corrects it through lightning fault data. Overlaying the risk level of the area and the distribution map of the pole-tower foundation coordinates, it will obtain the distribution of lightning hazard-pregnant risk at the pole-tower area, which would contribute to guiding the differentiated lightning protection transformation of the line. Compared to traditional unified lightning protection renovation methods, differentiated lightning protection methods that integrate factors such as pole-tower structure, wire type, and lightning risk level can achieve significant lightning protection effects at a lower economic cost. Taking Nanchang City as an example, risk assessment and lightning protection renovation were conducted on 21 distribution lines. The average number of lightning trips per year is 55 before the renovation, but it is only 4 after the renovation, which the number of lightning trips significantly reduce. This verifies the effectiveness of using lightning hazard-pregnant assessment results to guide differentiated lightning protection methods.